Vocabulary Mastery by Using Storytelling - Sektalonir Oscarini Bhakti; marwanto Marwanto Marwanto (Script Journal: Journal of Linguistics and English Teaching, 2018)
Abstract:  This research investigated 80 students of Diploma III Architecture of Samarinda State Polytechnic to see their vocabularies mastery trough storytelling. Telling the stories is one of the best way to find out the students' English Mastery. Some obstacles are also found in learning English trough performing storytelling in the class such as the suitable material and text for the students, the lack of ability of the students and the teacher in conducting story as well as the readiness and the nervousness of the storytellers. As an English lecturer, the researcher also finds that how to improve vocabularies is one of the students' problems in learning English.  It is proved when the students are asked to tell a story in front of the class. In this research, the students needed telling stories before they had the English vocabulary test.  From the test, it could be concluded that the highest score was 92 got by one (1) student while the lowest score was 46 got by one (1) student.  Meanwhile, the average score was 78 that classified fair (B).  There were two (2) students who got below 50 that classified Fail. The results show that even the students' English mastery were satisfied but the students still need to practice how to tell the story in a good way so that they will master in all aspects.Keywords: Samarinda State Polytechnic, Students' Mastery, Storytelling